Efficient reduction of peak-to-average power ratio in multiple-input multiple-output orthogonal frequency-division multiplexing system by shuffling cluster sequences - Mi, Si Sar; Mata, Tanairat; Boonsrimuang, Pornpawit; Boonsrimuang, Pisit (My University, 2024)
We propose a shuffling cluster sequence technique without separate side information (SI) for multiple-input multiple-output (MIMO) orthogonal frequency-division multiplexing (OFDM) systems. In the proposed technique, the active subcarriers over two consecutive OFDM symbols are divided into (Formula presented.) clusters, and each cluster (packet frame) includes a header for ID#cluster and payload for (Formula presented.). The (Formula presented.) clusters are shuffled to reduce the peak-to-average power ratio (PAPR) of the time-domain OFDM signal, which includes the information data and SI signals, with a low computational complexity. At the receiver, the information data can be correctly reconstructed by ID#cluster in the header of each cluster, achieving a smaller bit error rate than the conventional MIMO-OFDM system without PAPR reduction. Moreover, our technique is comparable with the conventional partial transmit sequence technique without the impact of a separate SI signal even when increasing the number of transmitter antennas in a nonlinear multipath fading channel.
Keywords: computational complexity; multiple-input multiple-output system; orthogonal frequency-division multiplexing; partial transmit sequence; peak-to-average power ratio; peak-to-average power ratio reduction